Pengaruh Net Interest Margin dan Non Performing Loan terhadap Return On Asset pada PT Bank Rakyat Indonesia (Persero) Tbk - Muhammad Rimawan; Dzaitun Mithaqain (Faculty of Economics, Universitas Internasional Batam, 2021)
This Study aims to determine the effect of Net Interest Margin and Non Performing Loan on Return On Asset at PT Bank Rakyat Indonesia (Persero) Tbk period 2010 until 2019. This type of research uses the associative method, with quantitative approach. Data collection techniques using secondary data in the form of a annual report. PT Bank Rakyat Indonesia (Persero) Tbk. Population was 16 years, the sampling technique used purposive sampling, and this samping used in this study 10 years from 2010 – 2019. The data analysis technique used multiple Linear regression, correlation ceofficient, determinatin ceofficient and hypotesis testing (T test and F test). The result show that the Net Interest Margin has a positive and significant effect on Return on Asset, Non Performing Loan has a negative and significant effect on Return on Asset, Net interest Margin and Non performing Loan has simultan have a effect on Return On Asset at PT Bank Rakyat Indonesia Tbk